2020
DOI: 10.3390/su12218906
|View full text |Cite
|
Sign up to set email alerts
|

Is Price an Indicator of Garment Durability and Longevity?

Abstract: Increasing focus on the sustainability of clothing has highlighted issues such as “fast fashion”, impacts of laundering, durability, perceptions and expectations of wear and quality. The general consensus is that low-price garments (usually “fast fashion”) are of low quality, low durability to laundering and are therefore more likely to be disposed of after minimal wears. The aim of this research is therefore to explore the relationship between price, perception of quality, frequency of laundering and durabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Furthermore, the impact of the fashion brands' attributes literature reveals that they have a significant positive impact on various aspects of the industry and society in terms of mitigating the environmental footprint [99], using eco-friendly materials [100], lowering energy and resource consumption [101,102], fair and ethical labor practices [103], safe working conditions [104], protecting workers' rights [105], providing transparency about sourcing and manufacturing [106], producing durable high-quality timeless garments [107], reducing over-consumption and waste [108], innovativeness [109], initiating the circular economy practices such as repairing [110], recycling [111], second-hand shopping [112], training the consumers [113], cooperating with the competitors to make an industry-wide shift to change the market [114], and engaging with the community to disseminate the local craftspeople [115] to contribute to sustainable practice.…”
Section: Sensitivity Analysis and Discussionmentioning
confidence: 99%
“…Furthermore, the impact of the fashion brands' attributes literature reveals that they have a significant positive impact on various aspects of the industry and society in terms of mitigating the environmental footprint [99], using eco-friendly materials [100], lowering energy and resource consumption [101,102], fair and ethical labor practices [103], safe working conditions [104], protecting workers' rights [105], providing transparency about sourcing and manufacturing [106], producing durable high-quality timeless garments [107], reducing over-consumption and waste [108], innovativeness [109], initiating the circular economy practices such as repairing [110], recycling [111], second-hand shopping [112], training the consumers [113], cooperating with the competitors to make an industry-wide shift to change the market [114], and engaging with the community to disseminate the local craftspeople [115] to contribute to sustainable practice.…”
Section: Sensitivity Analysis and Discussionmentioning
confidence: 99%
“…In a market-transformed global body politic geared toward capital(ist) accumulation, 'take-makewaste' production/consumption networks are predicated upon resource depletion and scarcity. Profit-hungry fast fashion corporations, fed by these linear supply chains, pump out low-priced and low-quality garments that are inevitably discarded by consumers after approximately seven or eight wears (Wakes et al, 2020) This politics of disposability is driven by the fickleness of clothing micro-trends on social media, engendering the shortening of textile lifespans (Burdsall, 2019). A report by McKinsey & Company (2016) demonstrates that fast fashion exists at a critical juncture where resource demand aggressively outstrips supply.…”
Section: Literature Review Talking Green Doing Greedmentioning
confidence: 99%
“…As can be seen in Wakes et al (2020), the practice of disposing of clothes is linked to the behavior of consumers. The authors observed that 50% of the interviewed consumers would discard a T-shirt after ten washes, as changes in color and modeling become noticeable.…”
Section: Main Trends In Recent Yearsmentioning
confidence: 99%